Teacher’s Belief about the Implementation of Curriculum 2013 in English Language - Ema Puspitasari; Bambang Widi Pratolo; Aulia Mufida Izzatul Mahfiana (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
This research was conducted to investigate teacher`s belief about the implementation of curriculum 2013 in English language teaching. The research method used in this research is descriptive qualitative involving four teachers of junior high schools as the subjects. The data were collected using open-ended interview as the instrument. The result of this research showed that there were many kinds of activities which were mostly done by all participants; (1) teachers’ beliefs about curriculum 2013 understanding, (2) teachers’ beliefs about reaction of the learners, and (3) teachers’ beliefs about assessment in curriculum 2013. The teachers believed that curriculum changes brought positive, innovative, and creative impacts on English for future education. Besides, changes in the current curriculum also give influence on the way teachers and students understand English learning from previously traditionally based learning to modern pedagogical dimension. Therefore, it can be concluded that teachers` belief about curriculum 2013 has an impact on its implementation in English language teaching.